Plants and tourism: Not seeing the forest [n]or the trees. (December 2019) - Cohen, Erik; Fennell, David
This article aims to explore an emergent sub-field in the study of tourism: the relationship between plants and tourism, which has been neglected in the literature. We discuss plants as a life form and confront the animal–plant divide, implicitly permeating tourism studies, with recent findings in biology and arguments in contemporary ontological anthropology, which seek to erase that divide and emphasize plant–animal continuity. We discuss the role of plants in the tourist experience and their place in differentially framed tourist settings, ranging from fully-natural to fully-contrived ones. We present the various ethical theories bearing on human conduct toward plants and indicate their applicability to tourism in the various settings. In conclusion we call for greater attention to the significant but overlooked role of plants in various touristic contexts.